Cardiac-Specific Overexpression of Caveolin-3 Attenuates Cardiac Hypertrophy and Increases Natriuretic Peptide Expression and Signaling - Horikawa, Yousuke T.; Panneerselvam, Mathivadhani; Kawaraguchi, Yoshitaka; Tsutsumi, Yasuo M.; Ali, Sameh S.; Balijepalli, Ravi C.; Murray, Fiona; Head, Brian P.; Niesman, Ingrid R.; Rieg, Timo; Vallon, Volker; Insel, Paul A.; et al. (Journal of the American College of Cardiology, 2011)
We hypothesized that cardiac myocyte-specific overexpression of caveolin-3 (Cav-3), a muscle-specific caveolin, would alter natriuretic peptide signaling and attenuate cardiac hypertrophy. Natriuretic peptides modulate cardiac hypertrophy and are potential therapeutic options for patients with heart failure. Caveolae, microdomains in the plasma membrane that contain caveolin proteins and natriuretic peptide receptors, have been implicated in cardiac hypertrophy and natriuretic peptide localization. We generated transgenic mice with cardiac myocyte-specific overexpression of caveolin-3 (Cav-3 OE) and also used an adenoviral construct to increase Cav-3 in cardiac myocytes. The Cav-3 OE mice subjected to transverse aortic constriction had increased survival, reduced cardiac hypertrophy, and maintenance of cardiac function compared with control mice. In left ventricle at baseline, messenger ribonucleic acid for atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) were increased 7- and 3-fold, respectively, in Cav-3 OE mice compared with control subjects and were accompanied by increased protein expression for ANP and BNP. In addition, ventricles from Cav-3 OE mice had greater cyclic guanosine monophosphate levels, less nuclear factor of activated T-cell nuclear translocation, and more nuclear Akt phosphorylation than ventricles from control subjects. Cardiac myocytes incubated with Cav-3 adenovirus showed increased expression of Cav-3, ANP, and Akt phosphorylation. Incubation with methyl-β-cyclodextrin, which disrupts caveolae, or with wortmannin, a PI3K inhibitor, blocked the increase in ANP expression. These results imply that cardiac myocyte-specific Cav-3 OE is a novel strategy to enhance natriuretic peptide expression, attenuate hypertrophy, and possibly exploit the therapeutic benefits of natriuretic peptides in cardiac hypertrophy and heart failure.